Treatment of experimental stroke with IL-10-producing B-cells reduces infarct size and peripheral and CNS inflammation in wild-type B-cell-sufficient mice - Bodhankar, Sheetal; Chen, Yingxin; Vandenbark, Arthur A.; Murphy, Stephanie J.; Offner, Halina (Metabolic brain disease, 2014)
Clinical stroke induces inflammatory processes leading to cerebral and splenic injury and profound peripheral immunosuppression. IL-10 expression is elevated during major CNS diseases and limits inflammation in the brain. Recent evidence demonstrated that absence of B-cells led to larger infarct volumes and CNS damage after middle cerebral artery occlusion (MCAO) that could be prevented by transfer of IL-10 + B-cells. The purpose of this study was to determine if the beneficial immunoregulatory effects on MCAO of the IL-10 + B-cell subpopulation also extends to B-cell-sufficient mice that would better represent stroke subjects. CNS inflammation and infarct volumes were evaluated in male C57BL/6J (WT) mice that received either RPMI or IL-10 + B-cells and underwent 60 min of middle cerebral artery occlusion (MCAO) followed by 96 h of reperfusion. Transfer of IL-10 + B-cells markedly reduced infarct volume in WT recipient mice when given 24 h prior to or 4 h after MCAO. B-cell protected (24 h pre-MCAO) mice had increased regulatory subpopulations in the periphery, reduced numbers of activated, inflammatory T-cells, decreased infiltration of T-cells and a less inflammatory milieu in the ischemic hemispheres of the IL-10 + B-cell-treated group. Moreover, transfer of IL-10 + B-cells 24 h before MCAO led to a significant preservation of regulatory immune subsets in the IL-10 + B-cell protected group presumably indicating their role in immunomodulatory mechanisms, post-stroke. Our studies are the first to demonstrate a major immunoregulatory role for IL-10 + regulatory B-cells in preventing and treating MCAO in WT mice and also implicating their potential role in attenuating complications due to post-stroke immunosuppression.